Uniqueness in nonlinear theory of porous elastic materials (Archives of Mechanics - Test, 1997)
This note is concerned with static deformations in a nonlinear theory of elastic materials with voids. First we extend some conservation laws to the nonlinear theory. A uniqueness result is presented under a condition related to the quasi-convexity assumptions.